The New Jim Crow in Higher Education: A Critical Race Analysis of Postsecondary Policy Related to Drug Felonies - Kenyon Whitman; Stephen Exarhos (Journal Committed to Social Change on Race and Ethnicity, 2020)
In this paper, critical race theory and critical race praxis for educational research are used to frame an analysis of the 1998 Amendments to the Higher Education Act of 1965 (HEA98) that limits access to financial aid for students who have been convicted of a drug felony. The authors explain how the HEA98 disenfranchises Black and Latinx college student populations. This policy is a form of institutional racism against the disproportionately large number of Black and Latinx individuals that have been convicted of drug-related crimes, which creates a caste system of college access and support. This policy analysis highlights data on incarcerated populations that link the policing of drug offenses to racial profiling and discrimination (e.g., “the War on Drugs” and the 1994 Crime Bill), questions the motivations for reducing access to education in drug offenders, reviews causes and inhibitors of recidivism in drug offenders to make the case for the promotion of education in recently-released offenders, and highlights empirical data that supports expanding access to these people. The authors conclude the paper with recommendations to progress toward racial educational equity. This paper is directed toward higher education scholars, practitioners, and policy makers who possess a strategic critical orientation towards racial equity in education.